Speed up the good deeds: new-normal Thailand and linguistic construction of Buddhist ‘Dana’ giving through a practice of ‘online merit-making’ - Thatdao Rakmak; Thanapas Dejpawuttikul; Kosit Tiptiempong (Cogent Arts & Humanities)
This article discusses the linguistic strategies shaped by the speed-up of online merit-making in Thailand’s post Covid-19. The study analyzes the language used in 100 online merit-making persuasion posts from various Facebook groups to uncover factors contributing to the acceleration of this linguistic phenomenon through Critical Discourse Analysis and Tomlinson’s sociological concept of speed and cultural immediacy. It uncovers patterns reflecting lingual acceleration that have not been systematically analyzed in previous studies on merit-making advertisement. Firstly, Thai words and phrases emphasizing urgency and immediacy exhibit prevailing beliefs and business ideology, urging prompt engagement in merit-making for immediate results. Secondly, invitation sentences employ language that emphasizes the calculable nature of merit-making, appealing to recipients’ reasoning and facilitating individualized participation. Lastly, emotionally charged words and expressions in charity advertisements evoke feelings of pleasure and relief, further stimulating participation in merit-making. The accelerating shift of lingual practice is enabled by technological advancements and social media. The examination of language strategies in digitalized merit-making provides readers with fresh insights into the changing pace of New-normal Thai society.